PENDIDIKAN NON FORMAL ANAK TERLANTAR (Studi Pada Yayasan Putri Gina Aceh) - , Zulfadli, S.Sos I ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Waif problem some area in Indonesia, becoming serious problem. Inclusive of in Acheh, waif in Acheh which is resulted from tsunami that happened at on date of 26 December 2004. But after tsunamis of waif existence become the attention from some Self-Supporting Institute of Society (NGO), especially NGO which is active in child enable ness. One of them is PKBM Putri Gina putting serious attention to waif existence. Waif handling conducted by this PKBM Putri Gina use the concept of education nonformal which its target to be powered waif and can fill the medial employment of society. Existence And activity of PKBM Putri Gina in giving waif education in Big Acheh area and Town of Banda Acheh, becoming to draw for writer to see the role institute the education of non-formal society in waif handling in realizing waif education. In this research is writer see in the PKBM Putri Gina role of all this waif activist and waif willingness learn this PKBM is good process and own the positive influence to be powered waif assumed of no use by some of society. So that writer have initiative for the checking of how strategy of study of education nonformal in PKBM Putri Gina to powered the waif, and what supplementary factor and resistor faced by the PKBM Putri Gina in waif handling and result of what reached by after education. Research method used to study the above problem is qualitative, with the technique of sampling sample aim to purposive sampling, to get the data naturally, by doing field research. This Design Research is descriptive qualitative, what is generally done at research in the form of case study, to depict problems in field and analyze it pursuant to obtained data. This research collects the data with three way of that is: observation, interview and documentation. Approach in this research use the approach phenomenology, to see the role a institute in handling of waif case seen by as shares participate and action to social phenomenon. To get the data validity in this research, researcher uses the technique Triangulat as audit technical data. Triangulation is audit technical of data authenticity exploiting something else outside that data for checking or as data comparator. Finding in research of education of nonformal of waif of PKBM Putri Gina use the certain method and strategy to reach the target expected. All educator use the method Bloom that is aspect Affective, Cognate and Psychomotor in handling and waif enable ness in course of realizing result which are positive to grad constructed and educated by the institute. In course of handling and waif enable ness, PKBM Putri Gina sharing with all limitation though there are atonal donor, but facility and educator energy must be improved. PKBM Putri Gina becomes one of institute tip of lance for society in powered waif. Process done good enough even also by applying cognate theory, affective and psychomotor will be able to yield the grad according to education standard. in realizing waif enable ness have a lot of bringing change which enough mean in develop